During the Covid-19 lockdown, rural residence is associated to healthier lifestyle behaviours in patients with chronic coronary syndrom. (11th May 2021) - Chague, F; Cransac-Miet, A; Boulin, M; Saint-Jalmes, M; Bichat, F; Soudry, A; Danchin, N; Zeller, M; Cottin, Y
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Dijon Football Côte d"Or OnBehalf: CLEO-CD Background: Lifestyle behaviours (LB) are keystones of coronary prevention and might be impacted during Covid-19 (C19) lockdown. Purpose: To compare the LB in urban and rural patients suffering from chronic coronary syndrom (CCS) Methods: 250 outpatients suffering from CCS were invited during the 6th week of the 1st C19 lockdown to answer to a phone-call questionnaire. Results: 220 questionnaires were fit for analysis, of whom about 1/4 declared a psychologic impairment; people staying at home in urban zones trended to be more impacted. Unhealthier behaviours including cigarette smoking, decrease in physical activity and increase in screentime were common, especially in patients from urban zones. Telehealth partially counterbalanced limitation in care access and none declared discontinuation of medications. Conclusion: The lockdown impacted wellbeing of CCS patients; living in rural zone was associated with a healthier LB.